Strategi Komunikasi Politik Dalam Pemenangan Prabowo-Gibran Pada Pemilu Presiden 2024 - Kontu, Fransin; Pesak, Stefanes (Universitas Musamus, Merauke, Papua, 2024)
This study examines the political communication strategy of the Prabowo-Gibran ticket in the 2024 Presidential Election, focusing on social media utilization, public image management, audience segmentation, and responses to critical issues. Using a descriptive qualitative method, this study analyzes social media content, news articles, and academic literature to understand their communication approach. The findings indicate that Prabowo-Gibran uses social media platforms such as Instagram, Twitter, and YouTube to spread campaign messages and engage directly with voters, especially the younger, digitally active generation. Their image is shaped by combining elements of firmness and innovation—Prabowo is portrayed as an experienced leader, while Gibran brings a modern and progressive youth appeal. Audience segmentation is implemented by tailoring messages to demographic characteristics, making campaign messages more relevant. Furthermore, quick responses to crisis issues help maintain a positive image and build public trust. In conclusion, a political communication strategy that integrates digital media, strong image management, and effective audience segmentation can enhance the appeal of the Prabowo-Gibran pair amid intense political competition.